Amari and the great game - Alston, B. B. (Alston, B. B. Supernatural investigations, 2022)
Amali Peters found her brother and saved all the supernatural world, and now is looking forward to her first summer as a Junior Agent. However, a fearsome new Head Minister who is strictly anti-magician, rivalries among the other Junior Agents, and the curse on her brother Quinton getting worse, it seems an easy summer just isn't in Amali's cards. When she refuses to join the secretive League of Magicians and take the chance to stand up for magiciankind, another magician steps forward, one with a dangerous plan that ignites the start of the Great Game to see who will succeed the Night Brothers.